Preparation method and application of multi-coordination covalent organic framework material
By designing multi-coordinated covalent organic frame materials, using their efficient adsorption and separation capabilities under acidic conditions, the problems of low stability, low adsorption amount and low selectivity of existing adsorption materials in thorium adsorption are solved, and efficient adsorption and separation of thorium ions are achieved.
Patent Information
- Application Number
- CN202510186663.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-20
AI Technical Summary
Existing adsorption materials have low stability, low adsorption amount and low selectivity in thorium adsorption, which limits the efficient separation and enrichment of thorium.
Using multi-coordinated covalent organic framework materials, two new 2D COFs materials, TBN-TS COF and TBN-TN COF are designed through the combination of nitrogen-rich amino group monomer and sulfur-rich monomer, and the N, O and S heteroatoms in their structures are used to strong coordination interactions with Th(IV) ions to achieve efficient adsorption and separation.
Under acidic conditions, the new multi-coordinated covalent organic frame material exhibits high adsorption capacity, excellent reuse performance and ultra-fast adsorption rate, which can achieve adsorption equilibrium within 30 minutes, solving the problems of low adsorption amount and poor recycling performance of existing materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a preparation method and application of a multi-coordinated covalent organic framework material. Background Art
[0002] Nuclear energy is a clean and low-carbon energy source. Uranium-based fuel is currently the main fuel for nuclear reactors and has been widely used in the nuclear power industry. However, with the rapid growth of human demand for energy and the limited uranium resources, the development and utilization of thorium-based nuclear fuel with abundant natural reserves has become increasingly important.
[0003] Thorium is a fertile nuclear material. 232 Th can be converted into nuclear fuel for direct use after neutron bombardment in the reactor. 233 U. In addition, thorium has the advantages of large reserves, easy refining, safety and greenness, and high fission energy, and is the most ideal substitute for uranium and plutonium. However, Th(IV) ions are chemically toxic and radioactive, which poses great harm to the environment and human health. Therefore, the effective separation and enrichment of Th(IV) in nuclear wastewater is the key to solving environmental pollution problems and realizing the efficient recycling of Th(IV) resources. Since thorium has similar chemical properties to rare earth elements and uranium, it is quite challenging to selectively adsorb and separate thorium from aqueous solution. The adsorption method is considered to be a technical means for effectively separating and recovering radioactive nuclides because of its advantages such as low cost, less secondary waste and high recovery rate. However, the low stability, low adsorption amount and low selectivity of the adsorption materials have always been the bottleneck restricting the development of this technology. Therefore, it is urgent to develop new solid adsorbents with high adsorption capacity and high adsorption selectivity for thorium.
[0004] Two-dimensional covalent organic frameworks (2D COFs) are a class of crystalline organic porous polymers with permanent porosity and highly ordered structures, with both hierarchical layered structures and one-dimensional open channels. Unlike other polymers, a notable feature of 2D COFs is that they can be pre-designed in structure. Among them, the topological design map provides geometric guidance for the structural tiling of the extended porous shape, and the condensation reaction provides a synthetic method for constructing pre-designed primary and higher-order structures. Over the past decade, chemical progress in these two areas has laid the foundation for the field of covalent organic framework materials. It is precisely because of the structural characteristics and diversity of 2D COFs materials that they have become the most promising materials for the adsorption and separation of metal ions.
[0005] At present, 2D COFs materials used in the field of thorium adsorption mainly chemically coordinate with Th(IV) through the N site on C=N, but the adsorption capacity is usually limited. Therefore, it is necessary to develop new organic framework materials, introduce more electron-rich groups into the 2D COFs skeleton, and design and prepare efficient COFs adsorbents with multiple adsorption sites to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the present invention proposes a preparation method and application of a multi-coordinated covalent organic framework material to solve the problems raised by the above-mentioned background technology.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A multi-coordinated covalent organic framework material, wherein the structural formula of the multi-coordinated covalent organic framework material 2D COFs is as shown in (I) or (II), (I) is TBN-TS COF, and (II) is TBN-TN COF:
[0009]
[0010]
[0011] Preferably, the preparation method of the multi-coordinated covalent organic framework material comprises the following steps: adding nitrogen-rich amine monomer, aldehyde monomer and organic solvent into a 10 mL Pyrex tube, ultrasonically treating for 30 minutes, and mixing to obtain a mixture; then adding a catalyst to the mixture, freezing it in liquid nitrogen, evacuating and filling it with nitrogen for multiple times, sealing the Pyrex tube with a flame gun while maintaining the vacuum state, cooling it to room temperature of 20 to 25°C, placing it in an oven for heating and crystallization, and then naturally cooling it to room temperature, filtering and collecting the solid, washing the solid with a solvent and extracting it overnight, heating and vacuum drying it, and then obtaining the multi-coordinated covalent organic framework material.
[0012] Preferably, the nitrogen-rich amine monomer is 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol (TBN); the aldehyde monomer is one of benzo[1,2-b:3,4-b':5,6-b']terthiophene-2,5,8-trialdehyde (TS) or 2,4,6-tris(4-formaldehydephenyl)-1,3,5-triazine (TN).
[0013] Preferably, the organic solvent is one of a mixed solution of mesitylene and 1,4-dioxane in a volume ratio of 0.5 to 10:1, a mixed solution of o-dichlorobenzene and mesitylene in a volume ratio of 0.5 to 10:1, and a mixed solution of o-dichlorobenzene and n-butanol in a volume ratio of 1 to 10:1.
[0014] Preferably, the molar ratio of nitrogen-rich amine monomer to aldehyde monomer in the mixture is 1-3:1; the volume mass ratio of the organic solvent and the sum of the nitrogen-rich amine monomer and the aldehyde monomer is 0.4-5.0 mL:14.4-86.40 mg.
[0015] Preferably, the catalyst is a 3-9 mol / L acetic acid solution, and the ratio of the molar amount of the nitrogen-rich amine monomer to the volume of the catalyst is 0.03 mmol: 0.01-1.0 mL.
[0016] Preferably, the reaction temperature of the heating crystallization is 70-150° C., and the reaction time is 1-7 days; the vacuum drying temperature is 80-150° C., and the drying time is 4-12 hours.
[0017] Preferably, the solvent in the solvent washing is at least one of tetrahydrofuran, acetone, methanol, N,N-dimethylformamide and 1,4-dioxane.
[0018] Preferably, the multi-coordinated covalent organic framework material of the present invention is used for the efficient adsorption of thorium ions and the separation and selection of thorium ions and uranium ions.
[0019] Preferably, the pH of the solution environment for adsorbing thorium ions is 4.0-5.0.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention uses the amino monomer 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol containing nitrogen and oxygen coordinated heteroatoms and sulfur-rich benzo[1,2-b:3,4-b':5,6-b']terthiophene-2,5,8-trialdehyde or nitrogen-rich 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer to prepare a multi-coordinated covalent organic framework material. This is the first synthetic report, and its structural formula has never been disclosed in the prior art.
[0022] (2) The multi-coordinated covalent organic framework material prepared by the present invention can realize the efficient adsorption and separation of thorium and thorium uranium ions under acidic conditions (pH 4.0-5.0) due to the strong coordination interaction between the abundant N, O, S heteroatoms in the framework structure and Th (IV). It not only has a high adsorption capacity and excellent reusability, but also exhibits an ultra-fast adsorption rate, reaching adsorption equilibrium within 30 minutes, thus solving the problems of low adsorption capacity and poor recycling performance of current thorium adsorption materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a synthetic route for the novel multi-coordinated covalent organic framework material according to the embodiment of the present invention;
[0024] Figure 2 PXRD spectra of two 2D COFs;
[0025] Figure 3 FT-IR spectra of two 2D COFs;
[0026] Figure 4 Nitrogen adsorption-desorption curves of two 2D COFs;
[0027] Figure 5 are the adsorption amount and removal rate of the two 2D COFs at different pH;
[0028] Figure 6 The adsorption kinetics of two 2D COFs;
[0029] Figure 7 are the adsorption isotherms of two 2D COFs;
[0030] Figure 8 The cyclic performance of two 2D COFs for thorium adsorption;
[0031] Fig. 9 XPS spectra of TBN-TS COF before and after thorium adsorption. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.
[0033] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0034] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0035] The nitrogen-rich amino monomer 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol (Cryst. Growth Des. 2019, 19, 3543-3550) used in the embodiment of the present invention can be synthesized by the method reported in the literature, benzo[1,2-b:3,4-b':5,6-b']trithiophene-2,5,8-trialdehyde can be purchased, and 2,4,6-tris(4-formylphenyl)-1,3,5-triazine can be purchased.
[0036] Example 1
[0037] In a 10 mL Pyrex tube, 20.66 mg (0.060 mmol) of 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol monomer, 13.22 mg (0.040 mmol) of benzo[1,2-b:3,4-b':5,6-b']terthiophene-2,5,8-trialdehyde monomer and 2 mL of a mixture of o-dichlorobenzene and n-butanol in a volume ratio of 1:1 were added to obtain a mixture, and the mixture was ultrasonically treated for 30 min. in, add 0.2 mL of 6 mol / L acetic acid solution of the catalyst, then freeze in liquid nitrogen, evacuate and fill with nitrogen three times, and seal the Pyrex tube with a flame gun while maintaining the vacuum state. After room temperature, place it in a 120°C oven for heating and crystallization for 3 days, then cool naturally to room temperature and collect the solid by filtration, wash with tetrahydrofuran solvent and extract overnight, heat to 120°C and vacuum dry for 10 hours to obtain a new multi-coordinated covalent organic framework material, which is a yellow-brown powder and named TBN-TS COF. For the synthesis route, see Figure 1 superior.
[0038] Example 2
[0039] In a 10 mL Pyrex tube, 10.33 mg (0.030 mmol) of 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol monomer, 13.22 mg (0.040 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer and 1 mL of a mixture of mesitylene and 1,4-dioxane in a volume ratio of 3:1 were added to obtain a mixture. After the mixture was ultrasonically treated for 20 min, 0.15 mL of a 6 mol / L acetic acid solution of the catalyst was added, and then frozen in liquid nitrogen. After vacuuming and filling with nitrogen three times, the Pyrex tube was sealed with a flame gun while maintaining the vacuum state. After room temperature, it was placed in a 120°C oven for heating and crystallization for 3 days, and then naturally cooled to room temperature. The solid was collected by filtration, washed with acetone solvent and stripped overnight, heated to 100°C and vacuum dried for 12 h to obtain a new multi-coordinated covalent organic framework material, which was a bright yellow powder and named TBN-TN COF. Synthesis route details Figure 1 Down.
[0040] Example 3
[0041] In a 10 mL Pyrex tube, 8.61 mg (0.025 mmol) of 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol monomer, 8.26 mg (0.025 mmol) of benzo[1,2-b:3,4-b':5,6-b']terthiophene-2,5,8-trialdehyde monomer and 0.4 mL of a mixture of o-dichlorobenzene and mesitylene in a volume ratio of 1:1 were added to obtain a mixture, and the mixture was ultrasonically treated for 30 min. Then, 0.2 mL of 3 mol / L acetic acid solution of the catalyst was added, followed by freezing in liquid nitrogen. After evacuating and filling with nitrogen three times, the Pyrex tube was sealed with a flame gun while maintaining the vacuum state. After room temperature, it was placed in a 150°C oven for heating and crystallization for 1 day, and then naturally cooled to room temperature and filtered to collect the solid. The solid was washed with N,N-dimethylformamide solvent and stripped overnight, heated to 150°C and vacuum dried for 4 hours to obtain a new multi-coordinated covalent organic framework material as a yellow-brown powder, named TBN-TS COF.
[0042] Example 4
[0043] In a 10 mL Pyrex tube, 51.65 mg (0.150 mmol) of 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol monomer, 16.53 mg (0.050 mmol) of benzo[1,2-b:3,4-b':5,6-b']terthiophene-2,5,8-trialdehyde monomer and 5.0 mL of a mixture of o-dichlorobenzene and mesitylene in a volume ratio of 1:1 were added to obtain a mixture, and the mixture was ultrasonically treated for 30 After 1.0 mL of 9 mol / L acetic acid solution of the catalyst was added, followed by freezing in liquid nitrogen, evacuating and filling with nitrogen three times, and then sealing the Pyrex tube with a flame gun while maintaining the vacuum state. After room temperature, it was placed in a 70°C oven for heating and crystallization for 7 days, and then naturally cooled to room temperature and filtered to collect the solid. The solid was washed with 1,4-dioxane solvent and stripped overnight, and heated to 80°C for vacuum drying for 12 hours to obtain a new multi-coordinated covalent organic framework material as a yellow-brown powder, named TBN-TS COF.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that the nitrogen-rich amine monomer 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol (TBN) is replaced by another amine monomer: 4,4'-diaminoterphenyl (SEB), and the other operations are consistent with Example 1.
[0046] Comparative Example 2
[0047] The difference between this comparative example and Example 1 is that benzo[1,2-b:3,4-b':5,6-b']terthiophene-2,5,8-trialdehyde (TS) is replaced by other aldehyde monomers: 1,3,5-tri(p-formylphenyl)benzene (TFA), and other operations are consistent with Example 1.
[0048] Comparative Example 3
[0049] The difference between this comparative example and Example 1 is that the nitrogen-rich amine monomer 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol (TBN) is replaced by other amine monomers: 1,3,5-tris(4-aminophenyl)benzene (THA), and the other operations are consistent with Example 1.
[0050] Experimental Example 1 Structure and property identification of multi-coordinated covalent organic framework materials
[0051] The powder of the novel multi-coordinated covalent organic framework material obtained in Example 1 and Example 2 was subjected to X-ray diffraction and interference pattern measurement and Fourier transformation to obtain an X-ray diffraction spectrum and a Fourier infrared spectrum (see Figure 2 , Figure 3 ), the X-ray diffraction pattern can be used to determine that the method of the present invention has successfully synthesized a new type of organic porous material with multifunctional coordination, and the Fourier infrared spectrum shows that the new type of multi-coordination framework material 2D COFs has a C=N bond stretching vibration peak, indicating that the Schiff base polycondensation reaction between the two monomers has successfully occurred to form an imine linking bond.
[0052] The nitrogen adsorption-desorption curves of the novel multi-coordinated covalent organic framework materials obtained in Example 1 and Example 2 are tested (see Figure 4 ), from which we can see that the S BET =901.05m 2 / g,d NLDFT =3.54nm, S of TBN-TN COF multi-coordination framework material BET =465.19m 2 / g,d NLDFT =3.58nm, both have larger specific surface area and pore size.
[0053] Experimental Example 2 Adsorption performance of thorium under different experimental conditions
[0054] 2.1 The calculation is based on the following formula:
[0055] Adsorption amount calculation formula:
[0056] Removal rate calculation formula:
[0057] Where: q e is the adsorption capacity of thorium at adsorption equilibrium, mg / g;
[0058] C0 is the mass concentration of thorium in the initial solution, mg / L;
[0059] C e is the mass concentration of thorium in the solution at equilibrium, mg / L;
[0060] V is the volume of the solution, L;
[0061] m is the mass of the adsorbent, g;
[0062] η is the removal rate, 100%.
[0063] 2.2 The 2D COFs materials prepared in Example 1 and Example 2 were subjected to adsorption experiments at different pH values, with a pH range of 1.0 to 5.0, an initial concentration of thorium solution of 100 mg / L, a solid-liquid ratio of 1:3, and an adsorption time of 24 h. The experimental results are shown in FIG. Figure 5 The materials of Example 1 and Example 2 reach a saturated adsorption capacity of 300 mg / g at a pH of 4.0, while these two materials do not adsorb or adsorb very little at a pH of 1 to 3.
[0064] 2.3 The 2D COFs materials prepared in Example 1 and Example 2 were subjected to an adsorption kinetics experiment. The initial concentration of the thorium solution was 100 mg / L, the solid-liquid ratio was 1:3, the pH was 4.0, and the adsorption time was 0 to 720 min. The experimental results are shown in FIG. Figure 6 As shown, the adsorption rate is very fast, and the adsorption equilibrium time is reached in 30 minutes. At the same time, it conforms to the pseudo-second-order kinetic model and belongs to a chemical adsorption process.
[0065] 2.4 The 2D COFs materials prepared in Example 1 and Example 2 were subjected to adsorption isotherm test. The initial concentration of the thorium solution was 50-500 mg / L, the solid-liquid ratio was 1:6, the pH was 4.0, and the adsorption time was 24 h. The experimental results are shown in FIG. Figure 7 The maximum saturated adsorption capacity of the materials prepared in Example 1 and Example 2 is close to 1500 mg / g, and it conforms to the Langmuir model and belongs to monolayer adsorption.
[0066] 2.5 A multi-component adsorption selectivity experiment was carried out on the 2D COFs materials prepared in Example 1 and Example 2. Different competing ions (such as uranium, samarium, lanthanum, praseodymium, rubidium, gadolinium, and lutetium) coexisted with thorium in a mixed solution. The concentrations of the competing ions and thorium were both 100 mg / L, the solid-liquid ratio was 1:3, the pH was 4.0, and the adsorption time was 24 h. The adsorption amount of multi-component elements was tested by ICP-OES (inductively coupled plasma optical emission spectrometer). The experimental results are shown in Table 1.
[0067] Table 1 Thorium and uranium separation selectivity SF of materials in Example 1 and Example 2 Th / U
[0068]
[0069] Thorium and uranium separation selectivity (SF Th / U ) is 12.73, and it hardly adsorbs samarium, lanthanum, praseodymium, rubidium, gadolinium and lutetium. Th / U ) is 13.52, and it hardly adsorbs samarium, lanthanum, praseodymium, rubidium, gadolinium and lutetium. Therefore, the multi-coordinated 2D COFs material prepared by the present invention can realize the selective adsorption and separation of thorium, and exhibits excellent adsorption selectivity and affinity for thorium.
[0070] 2.6 The 2D COFs materials prepared in Example 1 and Example 2 were subjected to a recycling performance test, and the adsorbed multi-coordinated 2D COFs materials were eluted with 0.1M HNO3. The experimental results are shown in Figure 8 As shown, it can be seen that the adsorption amount of the 2D COFs material remains almost unchanged after being recycled 5 times, indicating that the adsorbent material of the present invention has good cycle stability and high reuse rate.
[0071] 2.7 The 2D COFs material prepared in Example 1 was subjected to XPS performance testing, and the mutual coordination between Th(IV) ions and 2D COFs adsorbent was studied by XPS. The experimental results are shown in Fig. 9 As shown in the figure, after the adsorption of Th(IV) ions, the electron binding energy of the O1s and N1s orbitals of the 2DCOFs material increased, and new peaks were observed, which were attributed to the Th-O coordination bond and Th-N coordination bond, respectively; similarly, after the adsorption of Th(IV) ions, the electron binding energy of the S2p orbital of the 2D COFs material also increased, indicating that the electron cloud of S moved toward the Th(IV) direction and combined with Th(IV), and the new peak that appeared can be attributed to the Th-S coordination bond.
[0072] Example 3 Comparison of the adsorption performance of thorium
[0073] The 2D COFs materials prepared in Example 1, Example 2 and Comparative Examples 1 to 3 were taken to test the adsorption performance of thorium. The initial concentration of the thorium solution was 100 mg / L, the solid-liquid ratio was 1:6, the pH was 4.0, and the adsorption time was 24 h. The test results are shown in Table 2:
[0074] Table 2 Comparison of adsorption performance of thorium
[0075]
[0076] It can be seen from Table 2 that the adsorption performance of thorium prepared by the materials of Example 1 and Example 2 is 1497.3 mg / g and 1462.8 mg / g respectively; it can be seen from the comparison between Example 1 and Example 2 respectively that replacing TS or TN with TFA will lead to a significant decrease in the adsorption capacity of thorium ions; it can be seen from the comparison between Example 1 and Comparative Example 1 that replacing TBN with SEB will lead to a significant decrease in the adsorption capacity of thorium ions; it can be seen from the comparison between Example 2 and Comparative Example 3 that replacing TBN with THA will lead to a significant decrease in the adsorption capacity of thorium ions; it can be seen that the 2D COFs material prepared by the combination of TBN-TS and TBN-TN has the best adsorption performance for thorium.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-coordinated covalent organic framework material, characterized in that: The structural formula of the multi-coordinated covalent organic framework material 2D COFs is as shown in (I) or (II):
2. The method for preparing a multi-coordinated covalent organic framework material according to claim 1, characterized in that: The following steps are involved: Add nitrogen-rich amine monomer, aldehyde monomer and organic solvent into the tube, and mix them evenly by ultrasonication to obtain a mixture; then add a catalyst into the mixture, freeze it in liquid nitrogen, evacuate the tube, fill it with nitrogen, seal the tube with flame, cool it to 20-25°C, heat it for crystallization, collect the solid, wash the solid with solvent and dry it in vacuum to obtain a multi-coordinated covalent organic framework material.
3. The method for preparing a multi-coordinated covalent organic framework material according to claim 2, characterized in that: The nitrogen-rich amine monomer is 4,7-bis(4-aminophenyl)-α-methyl-1H-benzimidazole-2-methanol; the aldehyde monomer is benzo One of [1,2-b:3,4-b':5,6-b']trithiophene-2,5,8-trialdehyde or 2,4,6-tris(4-formylphenyl)-1,3,5-triazine.
4. The method for preparing a multi-coordinated covalent organic framework material according to claim 2, characterized in that: The organic solvent is one of a mixed solution of mesitylene and 1,4-dioxane in a volume ratio of 0.5 to 10:1, a mixed solution of o-dichlorobenzene and mesitylene in a volume ratio of 0.5 to 10:1, and a mixed solution of o-dichlorobenzene and n-butanol in a volume ratio of 1 to 10:
1.
5. The method for preparing a multi-coordinated covalent organic framework material according to claim 2, characterized in that: The molar ratio of the nitrogen-rich amine monomer to the aldehyde monomer in the mixture is 1-3:1; the volume mass ratio of the organic solvent to the sum of the nitrogen-rich amine monomer and the aldehyde monomer is 0.4-5.0 mL:14.4-86.40 mg.
6. The method for preparing a multi-coordinated covalent organic framework material according to claim 2, characterized in that: The catalyst is a 3-9 mol / L acetic acid solution, and the ratio of the molar amount of the nitrogen-rich amine monomer to the volume of the catalyst is 0.03 mmol: 0.01-1.0 mL.
7. The method for preparing a multi-coordinated covalent organic framework material according to claim 2, characterized in that: The reaction temperature of the heating crystallization is 70-150° C., and the reaction time is 1-7 days; the vacuum drying temperature is 80-150° C., and the drying time is 4-12 hours.
8. The method for preparing a multi-coordinated covalent organic framework material according to claim 2, characterized in that: The solvent in the solvent washing is at least one of tetrahydrofuran, acetone, methanol, N,N-dimethylformamide and 1,4-dioxane.
9. Use of the multi-coordinated covalent organic framework material according to claim 1 or the multi-coordinated covalent organic framework material prepared by the preparation method according to any one of claims 2 to 8 in the efficient adsorption of thorium ions and the separation and selection of thorium ions and uranium ions.
10. The use according to claim 9, characterized in that The pH value of the solution environment for adsorbing thorium ions is 4.0-5.0.
Citation Information
Patent Citations
Polyimide precursor and application thereof
CN113307971A
Benzotrithienyl covalent organic framework catalyst as well as preparation method and application thereof
CN115463687A
Preparation method and application of metal N-heterocyclic carbene functionalized covalent organic framework material
CN116082589A
Method for producing polyimide film, polyimide film, and polyimide metal laminate using the same
JP2012207147A